Business Information Technology Models for Women Farmer Group in Indonesia - Soehardjoepri; Muslichah Erma Widiana; Mahmudah Enny Widyaningrum (Procedia of Social Sciences and Humanities, 2021)
The existence of women farmer groups in the use of land for agriculture, such as existing fruit and vegetables, deserves a response to the follow-up, considering that the activities of women farmer groups have great potential. However, the professions as farmers and agricultural laborers, the income of female farmers and agricultural laborers does not necessarily depend on the season. With the ability to manage further processed agricultural products, they can have reliable income and use a marketing system that is adjusted to the times. This research is a model trial with the title "Business Information Technology Models for Women Farmer Group in Indonesia" with the aim of minimizing disparities in the village. By utilizing knowledge, skills and technology, it is hoped that poverty and disparity can be minimized or even eliminated. This research at a macro level provides benefits to stakeholders, namely human resources who supply raw materials, female farmers who are metamorphosed into entrepreneurs, so that domestic and foreign consumers will get superior regional products with high quality.